Language and health-related quality of life outcomes of children early-detected with unilateral and mild bilateral hearing loss - Carew, Peter; Shepherd, Daisy A.; Smith, Libby; Soh, Qi Rui; Sung, Valerie (Frontiers in Pediatrics, 2023)
We aimed to describe the language and health-related quality of life (HRQoL) outcomes of children early-identified with unilateral or mild bilateral permanent hearing loss. This was a cross-sectional community-based study of children with mild bilateral or unilateral permanent hearing loss (including unilateral auditory neuropathy spectrum disorder (ANSD)), drawn from a populationbased databank in Victoria, Australia. Enrolment in this databank is independent of early intervention and amplification approaches. Language and caregiver-reported HRQoL outcomes are described by type and degree of loss at three timepoints across child development: at age 2 years (n=255), 5-7 years (n=173) and 9-12 years (n=45). Across all age groups, average language outcomes were poorer than population normative scores by between a half to two thirds of a standard deviation. Children with mild bilateral hearing loss demonstrated poorer average language outcomes than children with unilateral hearing loss, particularly at younger ages. Children with unilateral ANSD showed language outcomes comparable to their peers with unilateral profound hearing loss. Children had poorer HRQoL psychosocial scores compared to physical scores, without obvious patterns of outcomes linked to degree or type of hearing loss. This study demonstrates children with early-identified unilateral or mild bilateral hearing loss have average language and HRQoL outcomes poorer than population normative expectations from an early age. These outcomes are observed at later ages across childhood. These findings provide a contemporary description of language and quality of life outcomes for children identified but not targeted by universal newborn hearing screening and raise questions of how to provide better support for these populations of children and their families.